Strategi Komunikasi Politik Anggota Legislatif Terpilih Partai Kebangkitan Bangsa Pada Pemilu 2019 di Salatiga - Awaludin Pimay (Institut Agama Islam Tribakti (IAIT) Kediri, 2023)
Political communication strategy is the spearhead of the success of an individual or organizational goal. Likewise, what happened in the elections in Salatiga, especially the PKB faction. The PKB faction prepares its strategy, even the legislative candidates themselves have different strategies but with the same goal, namely winning seats at the DPRD government level. In addition, the implementation of the political communication strategy itself must also be considered so that there is no overlap between the strategy and its implementation. The research aims to explore the success of the political communication strategy carried out by four legislative members from the PKB faction and to gain insight into political communication, especially political communication strategies. In this study, researchers used a qualitative method by taking a sample of the PKB faction with information on the four legislative members who won the 2019 election in Salatiga City. The information obtained comes from interviews with four sources, including PKB legislative members, PKB staff, evidence of activities, and supporting documents. The results of the study stated that the political communication strategy carried out by the four legislative members was in accordance with the planning model of Philih Lesly. Strategies are carried out neatly and in careful planning. Political communication strategies are used in several stages, including acceptance of strategies from parties, analyzing the community, formulating policies, planning activity programs, conducting communication activities to the community, seeing community responses, and evaluating the results of their strategies. Then the systematics of the application of the political communication strategy concerning the obstacle and support factors experienced by members of the legislature during the campaign.